(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
A study was carried out for a period for four months from January to April 2019 in eight fish farms at Mymensingh region of Bangladesh. The principal objectives were to study the health status of gulsha in four months from eight farms in Mymensingh region as well as month wise pathological changes of various organs of gulsha through clinical and histopathological observations. Clinical signs of fish were reddish lesion and mild injured in different parts of body, abrasion, whitish spots etc. Gills of fish showed more pathological changes than skin, muscle and liver. Histopathologically, gills of all fish species were more affected in Nuha Aqua Farm than other seven fish farms of Mymensingh in January and February. General gill pathology of the fishes was lamellar missing, haemorrhage and hypertrophy. Pathology of skin and muscle of the fishes from different farms included epidermal missing, necrosis, vacuum and loss of muscle. Fat bodies, necrosis, vacuum and haemorrhage were the common pathology of liver in the fishes from sampled farms of Mymensingh. Mainly fat bodies, vacuum and necrosis were found in Sharnalata Agro Fisheries, Relience Aqua Farm, Nuha Aqua Farm and Manju Aqua Farm. On the contrary, haemorrhage and necrosis were noticed in Chan Mia Fish Farm, Fish Seed Multiplication Farm; Maskanda and Setu Hatchery and Aquaculture in Tarakanda. In the months of March and April different organs of gulsha fish like gill, skin, muscle and liver were recorded almost normal structure from sampled fish farms. Fish were found to be affected during colder months of January and February. But, during March and April most of the fish were found normal and healthy. From field and laboratory observations it was revealed that the study area had potentiality for gulsha culture, although necessary measures need to be taken especially during winter season. Res. Agric., Livest. Fish.7(1): 139-151, April 2020